Environmental risk management and communication in an african context: the case of the Mozal bypass in Mozambique - Bussotti, L. (Cadernos de Estudos Africanos, 2014)
This article aims to analyze the way in which Environmental Risk is managed and communicated to local people in an African context. In particular, the article considers the experience of one of the largest multinationals that operates in Mozambique: Mozal (Mozambique Aluminum). In 2010, it decided to make a “bypass” at its two Fume Treatment Centres. For six months, Mozal had been authorized to discharge emissions into the air without any filters, possibly damaging human health. The article seeks to understand how the various parties involved, institutional or otherwise, acted in order to prevent, manage and communicate this risk. The study is developed at two levels: firstly, the debate on risk communication in the Mozambican context; secondly, the same debate but at international level. As a conclusion, it is possible to argue that the weak and formal model of democracy present in Mozambique did not make it possible to obtain guarantees that have been considered serious and significant at international level.